Membrane Topological Structure of Neutral System N/A Amino Acid Transporter 4 (SNAT4) Protein - Shi, Qian (American Society for Biochemistry and Molecular Biology, 2011)
Members of system N/A amino acid transporter (SNAT) family mediate transport of neutral amino acids, including l-alanine, l-glutamine, and l-histidine, across the plasma membrane and are involved in a variety of cellular functions. By using chemical labeling, glycosylation, immunofluorescence combined with molecular modeling approaches, we resolved the membrane topological structure of SNAT4, a transporter expressed predominantly in liver. To analyze the orientation using the chemical labeling and biotinylation approach, the “Cys-null” mutant of SNAT4 was first generated by mutating all five endogenous cysteine residues. Based on predicted topological structures, a single cysteine residue was introduced individually into all possible nontransmembrane domains of the Cys-null mutant. The cells expressing these mutants were labeled with N-biotinylaminoethyl methanethiosulfonate, a membrane-impermeable cysteine-directed reagent. We mapped the orientations of N- and C-terminal domains. There are three extracellular loop domains, and among them, the second loop domain is the largest that spans from amino acid residue ∼242 to ∼335. The orientation of this domain was further confirmed by the identification of two N-glycosylated residues, Asn-260 and Asn-264. Together, we showed that SNAT4 contains 10 transmembrane domains with extracellular N and C termini and a large N-glycosylated, extracellular loop domain. This is the first report concerning membrane topological structure of mammalian SNAT transporters, which will provide important implications for our understanding of structure-function of the members in this amino acid transporter family.